Microbiological And Physico-Chemical Changes During Fermentation Of Theobroma Cacao, L.: Isolation And Characterization Of Cocoa Lipase. - Samsumaharto, Ratna Agung (2000)
A study was carried out to examine microbiological and physicochemical changes during the fermentation of Theobroma cacao. Isolation, partial purification, characterization of cocoa lipase were also carried out. Results showed that several microbes were successfully detected during fermentation of cocoa beans. The maximum number of yeast colonies observed in fermented cocoa beans PBC 123 and 159 clones was 4.7 x 108 and 1.5 x 109 CFU/g. fro wt., respectively. Acetic acid bacteria we·re found to be dominant, 9.6 x 107 CFU/g. fro wt. for PBC 123 clone and 1.4 x 108 CFU/g. fro wt. for PBC 159 clone during the third day of fermentation whilst moulds were present throughout the fermentation period of six days. Spore forming bacteria appeared to be dominant on the fifth day of fermentation period. The maximum number of colonies observed for lactic acid bacteria was 3.5 x 106